Marginal Bone Loss Around Early-Loaded SLA and SLActive Implants: Radiological Follow-Up Evaluation Up to 6.5 Years - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Purpose: The aim of this study was to compare marginal bone loss around early-loaded SLA and SLActive tissue-level implants (Straumann Dental Implants; Institut Straumann AG, Basel, Switzerland) after a mean of 81-month follow-up period. Material and Methods: One hundred seven SLA and 68 SLActive implants were placed in 55 patients and loaded with final restoration after 8 and 3 weeks of healing time, respectively. Marginal bone loss around implants was determined radiographically at initial and after a mean observation time ranging between 20 and 81 months. The effect of location (mandible vs maxilla), smoking habit, sex, implant length and diameter, and the type of prosthesis on the marginal bone loss was evaluated. Results: The overall cumulative survival rate was 98.2% being 99% for SLA implants and 97% for SLActive implants. After 20-month follow-up period, mean marginal bone loss values for the SLA and SLActive implants were 0.24 and 0.17 mm, respectively. After 81 months, mean marginal bone loss for the SLA and SLActive implants reached 0.71 and 0.53 mm, respectively. Marginal bone loss was affected by the length and type of implant and patients' smoking habit after a mean observation time of 20 months. However, none of the parameters had any significant effect on the marginal bone loss after a follow-up period of 81 months. Conclusion: With both SLA and SLActive implants, successful clinical results could be achieved up to 6.5 years of follow-up period.
Keywords: bone resorption; implant length; smoking; survival; SUBMERGED TITANIUM IMPLANTS; ACID-ETCHED SURFACE; LONG-TERM SURVIVAL; DENTAL IMPLANTS; PROSPECTIVE MULTICENTER; STRAUMANN IMPLANTS; POSTERIOR JAWS; CLINICAL-TRIAL; ORAL IMPLANTS; ITI IMPLANTS